Implementation of Student Management at MA Ma'arif 04 Kalirejo Lampung Tengah - Hasanah, Uswatun (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2018)
This study discusses the students' management of activity programs at  MA Ma'arif 04 Kalirejo, central Lampung. Data collection was done by using interview, observation and documentation. This is  a kind of a field research by using descriptive-qualitative approach. Sources of research data included representatives of the madrasa vice principal of student affairs, teachers and administrative staff. The result shows that the management implementation of students in MA Ma'arif 04 Kalirejo, Central Lampung has been carried out well. This can be seen from the existing indicators regarding student management, namely: analysis of the needs of students, recruitment of students including formation of the committee, formulating registration requirements, dissemination of information, providing form registration, registration and registration, selection of students, orientation, grouping of students, coaching and development of students including  discipline of students, extra curricular activities, guidance and counseling, special services, recording and reporting, as well as graduates and alumni.